2007
DOI: 10.1270/jsbbs.57.281
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Observation and High Temperature Rescue from Hybrid Weakness in a Cross between Japanese Rice Cultivars and Peruvian Rice Cultivar 'Jamaica'

Abstract: The weak growth occurring in hybrids derived from crosses between two normal strains is referred to as hybrid weakness. F 1 hybrid weakness (F 1 HW) in a cross between a Peruvian rice cultivar 'Jamaica' and Japanese rice cultivars has been reported and was considered to be controlled by a set of complementary genes, Hwc1 and Hwc2. We observed the development of F 1 plants between Nipponbare and Jamaica (NJF 1 s). NJF 1 s were characterized by short roots, rolled leaves and a short stature. Although the NJF 1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…And the photosynthetic rate of the HW F 1 was significantly lower than those of the parents. Currently, several hybrid weakness or necrosis cases in some plants were previously reported to be temperature sensitive [8] and high temperature could rescue hybrid weakness [17]. Autoactivation of immune responses associated with Arabidopsis hybrid breakdown at low temperature has been described [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the photosynthetic rate of the HW F 1 was significantly lower than those of the parents. Currently, several hybrid weakness or necrosis cases in some plants were previously reported to be temperature sensitive [8] and high temperature could rescue hybrid weakness [17]. Autoactivation of immune responses associated with Arabidopsis hybrid breakdown at low temperature has been described [8].…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid weakness induced by low temperature will affect the application of heterosis in hybrid rice, to some extent, especially in the double-cropping rice areas of South China, although the frequency of hybrid weakness in rice is apparently much lower than that of intraspecific crosses in Arabidopsis [8]. Hybrid weakness in rice was reported more than four decades ago and its occurrence was sometimes conditioned by low temperature [17]. These hybrid weakness cases showed similar symptoms, including stunted growth, fewer tillers and abnormal root development.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype differs considerably from that of hybrids carrying both Hwc1-1 and Hwc2-1, of which the symptoms are characterized by root growth inhibition appearing just 5 days after germination (Ichitani et al 2001;Saito et al 2007).…”
Section: Introductionmentioning
confidence: 89%
“…The genotypes of each recombinant were estimated to be Hwc2-1/Hwc2-1 if all hybrid plants showed inhibition of root elongation (usually less than 1 cm), hwc2-2/hwc2-2 if they showed normal root elongation (usually more than 5 cm), and Hwc2-1/hwc2-2 if hybrid plants segregated. A few intermediate phenotypes were transplanted in pots and grown for 1 month to check if hybrid weakness symptom as reported in our previous paper (Saito et al 2007) was observed or not. The genotypes of internal DNA markers between the two initial encompassing markers of HWC2 (Table 3) were tested to narrow down the area of interest.…”
Section: Mapping Strategymentioning
confidence: 97%